Experiences and Perceptions of Indonesian Language Education Study Program Students in Writing Folktales - Hidayah Budi Qur'ani; Candra Rahma Wijaya Putra; Fajar Rizki Darmawan; Elvina Anjarini (Lembaran Ilmu Kependidikan, 2025)
This study aims to understand how Indonesian Language Program students contribute to Indonesian literature through the Nusantara Literature curriculum. This research focuses on students' experiences, motivations, knowledge, and skills in influencing literature through Nusantara Literature. This research also reveals that the majority of students have a strong interest in literature, despite not having a strong background in literature. This research is a descriptive qualitative research. Qualitative descriptive research is research that. This research uses questionnaire data analysis which aims to describe students' experiences and perceptions in writing folklore. The subjects of this research were students of the Indonesian Language Education Study Program, Faculty of Teacher Training and Education, University of Muhammadiyah Malang. Students who became research subjects amounted to 28 people. The data collection techniques in this study are divided into two, namely primary data collection and secondary data. The data analysis technique in this research is thematic analysis to identify patterns from the questionnaire responses. This knowledge helps students understand local culture, improve their writing skills, and motivate them to be actively involved in literature through the Nusantara Literature curriculum. This research also highlights the importance of knowledge about literature, including its development, structure, and differences with modern literature. Students understand that literature is a unique component of the country's culture and history, and serves as a medium to teach moral and traditional values. The research also highlights the importance of creativity and motivation in literature, as it helps students develop ideas, understand the challenges of writing, develop their own genres, and motivate themselves to engage in literature. This leads to improved quality and creativity in writing, which ultimately contributes to the development of the Indonesian language.